Evaluating Global Atmospheric Inversions of Terrestrial Net Ecosystem Exchange CO2 Over North America on Seasonal and Sub‐Continental Scales. Issue 18 (23rd September 2022) - Cui, Yu Yan; Zhang, Li; Jacobson, Andrew R.; Johnson, Matthew S.; Philip, Sajeev; Baker, David; Chevallier, Frederic; Schuh, Andrew E.; Liu, Junjie; Crowell, Sean; Peiro, Hélène E.; Deng, Feng; et al.
Abstract: Atmospheric inversion estimates of net ecosystem exchange (NEE) of CO2 are increasingly relevant to climate policy. We evaluated sub‐continental, seasonal estimates of CO2 NEE from nine global inversion systems that participated in the Orbiting Carbon Observatory‐2 model intercomparison project (OCO‐2 v9 MIP), using 98 research flights conducted over the central and eastern United States from 2016 to 2018 as part of the Atmospheric Carbon and Transport ‐ America mission. We found that the seasonal amplitude of NEE in the central and eastern United States is underestimated in these models and model‐data biases are largest for those inversions with the smallest seasonal flux amplitudes. These results were independent of whether the inversions used satellite or in situ data. The largest NEE biases were observed in the Midwest croplands and eastern forests. Future experiments are needed to determine the causes of the persistent biases and if they are associated with biases in annual flux estimates. Plain Language Summary: The exchange of CO2 between terrestrial ecosystems and the atmosphere is an important component of the Earth's climate system. Atmospheric budgets are used to quantify this exchange globally, but these estimates are difficult to evaluate on a regional basis. We used a unique set of aircraft data to evaluate a set of state‐of‐the‐science estimates of ecosystem‐atmosphere CO2 exchange in temperate North America. Nearly every estimate underestimated the seasonal amplitude of ecosystem‐atmosphere CO2 exchange (net photosynthesis too weak in the summer; respiration too weak in the winter) in this region. The source of atmospheric CO2 data did not influence this finding. More study is needed to determine both the cause of these seasonal biases and the impact of this bias on annual net CO2 flux estimates. Key Points: The seasonal amplitude of net ecosystem exchange (NEE) of CO2 in the central and eastern temperate North America is underestimated in global atmospheric inversions The seasonal bias is not significantly different between inversions using OCO‐2 v9 land nadir/glint observations and in situ observations The largest NEE biases are observed in U.S. croplands and eastern forests